A Multisite Study Evaluating the Benefits of Early Intervention via Telepractice. Issue 2 (April 2017) - Behl, Diane D.; Blaiser, Kristina; Cook, Gina; Barrett, Tyson; Callow-Heusser, Catherine; Brooks, Betsy Moog; Dawson, Pamela; Quigley, Suzanne; White, Karl R.
Abstract : This study sought to determine the effectiveness of telepractice as a method of delivering early intervention services to families of infants and toddlers who are deaf or hard of hearing. A comparison group design was applied to ascertain the child, family, and provider outcomes via telepractice compared with traditional in-person home visits. A total of 48 children and their families, along with 15 providers from 5 early intervention programs, across the country participated. Children in the telepractice group received more intervention, although the number of prescribed sessions was equal across groups. Analyses of covariance demonstrated that children in the telepractice group scored statistically significantly higher than children in the in-person group on the PLS-5 Receptive Language subscale and PLS-5 Total Language standard scores, and the groups scored similarly on other language measures. There were no statistically significant differences between groups in regard to family outcomes of support, knowledge, and community involvement. Analysis of video recordings of telepractice versus in-person home visits resulted in higher scores for provider responsiveness and parent engagement. This study supports the effectiveness of telepractice in delivering early intervention services to families of children who are deaf or hard of hearing. Further research involving randomized trials with larger, more diverse populations is warranted.